KESILAPAN PENGUCAPAN KOSAKATA DALAM MEMBACA TEKS FABEL OLEH PEMELAJAR BIPA KELAS BINDO LEVEL A1 - Bagus Devanda Putra Mildan; Agus Syahrani; Mellisa Jupitasari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractVocabulary Pronunciation Skills in Reading Fable Texts by BIPA CLASS BINDO Students Level Al. Thesis. Department of Language and Arts Education. Indonesian Language Education Study Program. Faculty of Teacher Training and Education. Pontianak Tanjungpura University. The problem of this research is the pronunciation mistakes of vocabulary and the factors that influence the reading of fable texts by BIPA KELAS BINDO students level A1. The aim of the study in general was to describe the speech of vocabulary in reading fable texts by BIPA KELAS BINDO level A1 students. Its specific objective is to describe the inconvenience of vocabulary pronunciation and the factors that affect the pronunciation errors of vocabulary. The method used in this research is descriptive method. The form of this research is qualitative. The research data collection was carried out using the tes technique. Sources of data in this study were foreign speakers from three countries, namely Egypt, the Philippines, and the United States of America. Based on the research data, the conclusion is that BIPA KELAS BINDO level Al students have a reduction in phonemes, the addition of phonemes, and the replacement of phonemes, the factors that influence are the first language of each student. Then the output of this research can be in the form of a practical guide to teaching basic Indonesian for foreign studentsKeywords: BIPA, KELAS BINDO, level A1